Dissipation Pattern and Residue of Fenvalerate in Tea of Bangladesh (Dhaka University Journal of Science, 2015)
Fenvalerate, a non-systematic insecticide is extensively used for protection of tea leaves in Bangladesh. Excessive use of insecticides with improper pre-harvest intervals may cause the tea unsuitable for consumption and trade. The study was designed to determine the safe per-harvest interval after the application of fenvalerate on tea trees at two different doses. Fenvalerate was applied on tea plants in experimental plots at the full and half of the recommended doses (0.1 kg a.i /ha and 0.05 kg a.i /ha, respectively). Tea leaves were collected at 0 (2 h after application), 1, 3, 5, 7, 10 and 14 days after application of the insecticide and made into black tea which was infused with hot water. Both brew and brew free residue were extracted, cleaned up and analyzed by GC-ECD. The residue levels in the brew were 0.189, 0.033 and 0.007 mg/kg at zero, 7 and 10 days, respectively, when it was applied at half of the recommended dose. In case of the recommended dose, residue levels were 0.644 and 0.010 mg/kg at 0 and 10 day, respectively. Residues were below the maximum residue level (MRL: 0.1 mg/kg) on 5 day at half of the recommended dose and on 7 day at recommended dose. Dissipation of fenvalerate followed first order kinetics at both doses with half lives of 2.6 days in brew part and 4.6 days in brew free part. Recoveries were 6.56±0.003% and 90.6±0.033% in brew part and brew free residue part, respectively, giving a total recovery of 96.6±0.036%. LOD and LOQ were 0.002 and 0.006 mg/kg, respectively.Dhaka Univ. J. Sci. 63(2):73-76, 2015 (July)